Evaluation of the completeness and timeliness nutrition surveillance data reporting in Wonogiri district, Central Java province, 2017 - Ika Puspita Asturiningtyas; Trisno Agung Wibowo; Suprio Heryanto (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Some of the nutrition problems still found in Wonogiri district. To solve that problems, completeness, and timeliness of the nutrition surveillance data reporting are needed so the data can be used as the basis for making policy appropriately. Evaluation of nutrition surveillance system was conducted to find out completeness and timeliness of the nutrition surveillance data reporting. This was an evaluative study using quantitative descriptive analysis which conducted from December 2017 to January 2018. Subjects of this study were nutritionists in District Health Office and 25 Primary Health Care (PHC) which selected randomly using Slovin samples size. Data collected by interviews and observation on surveillance data reporting form. PHC that reported complete data were 6 PHC (24%). One PHC (4%) did not report malnutrition data due to poor of time management. Ten Puskesmas (40%) did not report Hemoglobin data because they assumed that it was the duty of the laboratory officer or midwife. Three PHC (12%) did not report exclusive breastfeeding data every month, because they consider that the data should be collected only once every six months. Nine PHC (36%) did not report goiter data because they considered that it was no need to report if no cases. Most PHC (52%), never report the data timely. Most nutritionists (84%) had another duty that inhibits them to finish the surveillance data timely. Only two PHC (8%) whom the nutritionists had another duty but always report the data timely. Completeness and timeliness of the nutrition surveillance data reporting were still unsatisfying. PHC should be encouraged to collect data completely and timely. The data collection procedure should be fixed on the indicator collected and the time period in the data collection.